The influence of microstructure and heat treatment on tool wear when machining wrought and additively manufactured Alloy 718 - Hajali, Tina (My University, 2020)
Additive Manufacturing (AM) as a rapidly growing technology offers unique opportunities for fabrication of metallic components in comparison with the conventional manufacturing processes. Post-processing is often required for the additively manufactured components to obtain the desired mechanical properties and to adjust the functional surface properties. Machining is one of the key post-processing methods that is performed to improve the surface finish properties and to set the dimensional tolerances of additively manufactured components. Many studies have been conducted to optimize the AM technologies for the fabrication of metallic parts, however, little information is available on the optimized strategies for machining of additively manufactured components. In this study, wear behavior of cemented carbide tools was investigated for machining of additively manufactured Alloy 718. The tool wear behavior was compared with that of the wrought test-pieces as the reference case. A number of test samples were initially fabricated using Laser-Beam Powder Bed Fusion (LB-PBF) and Electron-Beam Powder Bed Fusion (EB-PBF) methods. The tool wear investigations were conducted for the as-received and the heat-treated (solutionized + double aged) materials. Two different cemented carbide tools (coated and uncoated) with a similar geometry were used in the machining operation and for each tool-workpiece material combination, two different cutting conditions were investigated. Prior to the machining experiments, the microstructure of the workpiece materials was studied using light optical and scanning electron microscopy. Machining tests showed a very distinctive tool wear behavior when machining LB-PBF, EB-PBF and wrought samples. Between these three variations of workpiece materials, the EB-PBF and LP-PBF samples resulted, respectively, in the highest and the lowest tool wear rates in most cases. Moreover, the coated tools showed reduced wear rates while the solutionizing and double-aging treatment led to higher wear rates in most cases. The microstructural assessments showed that the samples manufactured by various techniques differed in grain size, type and amounts of micro-constituents and hardness values in as-received conditions. However, heat treatment did not cause noticeable changes in the grain size, type, size and amounts of those micro constituents but the hardness values increased as a result. Overall, the differences in tool wear behaviors when machining different variations of the material are believed to be mainly due to the differences in the type, size and amounts of micro-constituents and the large differences in the grain size. However, other factors like the differences in cutting temperatures and cutting forces can also be the reason for higher wear rates when machining heat-treated samples. More in depth investigations are needed to reveal the relative importance of all these factors on tool wear when machining additively manufactured Alloy 718.
Keywords: Additive Manufacturing; Machining; Turning; Alloy 718; Heat treatment